Corporate responsibility, ethics and accountability. Issue 1 (5th March 2018) - Odongo, Nickson Hebert; Wang, Daoping
Abstract : Purpose: This study aims to ascertain the magnitude to which real corporate responsibility (CR), ethics and accountability practices exist in Kenyan corporations. Design/methodology/approach: The insights of qualitative and quantitative approaches are investigated through descriptive and exploratory study carried out on 193 Kenyan companies in the corporate sector and 5 focus groups discussions comprising 9 members each. Findings: The paper divulged that current practices on CR, ethics and accountability are relatively low, as only senior managers underwent training on ethics; accountability was broadly perceived as resources accounting instead of actual accountability; and responsibility is highly skewed toward senior management at the expense of stakeholders and society in which they thrive. Research limitations/implications: The concept of sustainability has not been emphasized as a dimension of CR, ethics and accountability. Fresh opportunities of inquiry are extended considering this aspect. Practical implications: This study affirms practices that have a positive effect on corporate stakeholders, communities and environment. Social implications: This study strives to develop approaches of managing and controlling, ensuring that the welfare of stakeholders and society as a whole is uplifted and sustained. Originality/value: The conception of CR, ethics and accountability practices signifies a theoretical innovation.